Hailey‐Hailey Disease: An Updated Review With a Focus on Therapeutic Mechanisms - Mahesh Mathur; Sumit Paudel; Nabita Bhattarai; Sambidha Karki; Sandhya Regmi (Health Science Reports, 2025)
ABSTRACT Background Hailey‐Hailey disease (HHD), or familial benign chronic pemphigus, is a rare autosomal dominant genodermatosis characterized by chronic, painful, erythematous, erosive plaques and fissures at sites of friction such as the neck, axilla, groin, and perineum. The pathogenesis is due to a mutation in the ATP2C1 gene, which encodes the human secretory‐pathway calcium/manganese‐ATPase isoform 1 (hSPCA1) that regulates calcium and manganese concentration in the Golgi apparatus. The diagnosis relies on clinical presentation and characteristic histopathological features, notably a “dilapidated brick wall” appearance. There is no cure for this genodermatosis and main aim of management in HHD is to control symptoms and reduce recurrence. Multitude of topical, systemic agents, procedural therapy such as laser therapy and surgery for the treatment of HHD have been reported in the literature. Aims This comprehensive review aims to discuss the efficacy of current HHD treatments with special focus on therapeutic mechanisms. Conclusion This review highlights clinical and histological features of HHD and offers guidance for dermatologists involved in managing this distinct dermatosis.